1989
DOI: 10.1002/mrm.1910110106
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial creatine kinase exchange rates and 31P NMR relaxation rates in intact pigs

Abstract: In this study, we used 31P NMR to investigate the relationship between cardiac workload and creatine kinase flux in intact pigs. NMR measurements were performed on anesthetized miniature swine in which a surface coil was surgically implanted on the surface of the left ventricle. Cardiac workload was varied by infusion of norepinephrine. Phosphate exchange between creatine phosphate and ATP was measured by a combined saturation transfer, saturation recovery pulse sequence. Exchange measurements showed that crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 19 publications
4
11
2
Order By: Relevance
“…Whereas mean myocardial CK flux is slightly higher at 3.3 Ϯ 1.2 vs. 2.8 Ϯ 0.7 mol͞g per sec (P ϭ 0.22), this increase is not statistically significant and is not proportionate to the doubled rate-pressure product. The finding that CK flux does not significantly increase with cardiac workload over a physiologic range in humans is different from that seen in isolated rat hearts (25) but similar to prior studies performed in vivo in sheep, pigs, and dogs (18,19,26,27).…”
Section: Resultssupporting
confidence: 65%
“…Whereas mean myocardial CK flux is slightly higher at 3.3 Ϯ 1.2 vs. 2.8 Ϯ 0.7 mol͞g per sec (P ϭ 0.22), this increase is not statistically significant and is not proportionate to the doubled rate-pressure product. The finding that CK flux does not significantly increase with cardiac workload over a physiologic range in humans is different from that seen in isolated rat hearts (25) but similar to prior studies performed in vivo in sheep, pigs, and dogs (18,19,26,27).…”
Section: Resultssupporting
confidence: 65%
“…The effect o f N E , presented in this report, is a decrease in PCr, which is in contrast to earlier work [30,31], Some o f the earlier data which was done on pigs can be consid ered to be preliminary in that the number of experiments and the physiological controls were not optimal [30], The work o f Katz et al [31] is on dogs and is carefully done. However, the protocols are somewhat differ ent.…”
Section: Discussioncontrasting
confidence: 53%
“…K f and flux varied with work load [28], In other studies o f the perfused rat heart [29], the flux through the C K reaction was found to be proportional to M V CK In the intact pig. on the other hand [30], an essentially con stant K f was found for the C K reaction un der a wide (2.5-fold change) variation of H R X SBP induced with N E. Furthermore, since no change in the levels o f PCr was found, the flux o f PCr A T P was constant as well. This result was confirmed using ca nine hearts in vivo [31].…”
Section: Discussionmentioning
confidence: 71%
“…The surprising finding of similar T 1's for CP and ATP resonances under our experimental conditions cannot be easily explained. It must, however, be mentioned, that none of the previous animal work (3)(4)(5)(6)(7)(8)(9)(10) 2.8, 3.3, and 3.6 s. In contrast, rabbit skeletal muscle examined at 4.7 T showed Tl's for CP and [y-PIATP of 1.9 and 0.7 s, respectively ( 2 4 ) . Thus, although Tl's for both CP and ATP are increased as field strength is decreased, it appears that the field dependence of T 1 ATP is more pronounced than that for T lCp.…”
Section: Discussionmentioning
confidence: 72%
“…Although spin-lattice relaxation times (T 1 's) of phosphorus metabolites visible in 31P-MR spectra are well defined for animal and human skeletal muscle ( 1 , 2), and TI'S for cardiac muscle have been determined in various animal studies (3)(4)(5)(6)(7)(8)(9)(10), T1 values of phosphorus metabolites in human myocardium have not been reported. This may be due to the fact that human 31P-MR spectra necessitate long acquisition times, and measurement of TI'S requires acquisition of a number of consecutive spectra.…”
Section: Introductionmentioning
confidence: 98%